2015
DOI: 10.4236/oalib.1101572
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Head Librarians’ Leadership Styles on Job Satisfaction of Librarians’ in Tertiary Institution Libraries in Imo State, Nigeria

Abstract: A general opinion that is supported by research is that leadership style in any organization exerts a major influence on the structure, strategy and well being of the organization. In the library environment therefore, the influence of leadership style on the job satisfaction of librarians is very crucial to the success of the library. Common observations from informal interactions with librarians who work in the libraries show that leadership styles in tertiary institution libraries in Imo state are poor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…This was an indication that library heads in Benue state practised different types of LSs at varying degrees. This finding was in agreement with Nwaigwe (2015) who also reported that head librarians in tertiary institutions in Imo state, Nigeria practised more of democratic LS than autocratic and laissez-faire. However, this finding was not in congruent with Idiegbeyanose (2018) who reported librarians in South-West, Nigeria practised autocratic style of leadership.…”
Section: Review Of Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…This was an indication that library heads in Benue state practised different types of LSs at varying degrees. This finding was in agreement with Nwaigwe (2015) who also reported that head librarians in tertiary institutions in Imo state, Nigeria practised more of democratic LS than autocratic and laissez-faire. However, this finding was not in congruent with Idiegbeyanose (2018) who reported librarians in South-West, Nigeria practised autocratic style of leadership.…”
Section: Review Of Literaturesupporting
confidence: 91%
“…Nwaigwe (2015) conducted a study to examine the influence of head librarians’ LS on job satisfaction of librarians in tertiary institution libraries in Imo state, Nigeria. The study adopted survey design using 61 librarians.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Leadership has, however assumed greater importance in today's organization including the library because of emerging force of globalization, technological innovations and workers expectations (Nwaigwe, 2015). These forces require dynamic and efficient leadership, anchored on strong ability to, not only combine resources in the most efficient ways, but to build a formidable work force that will work with enthusiasm for the achievement of goals.…”
Section: Introductionmentioning
confidence: 99%
“…It also agrees with the findings of Iyaiya (2000) and Ezeuwa (2005), where they concluded that democratic leaders see their subordinates as colleagues and partners in progress with objective ideas for solving organizational problems. Nwaigwe (2015) in her findings revealed that though democratic leadership style is commonly adopted by head librarians autocratic and laissez-faire leadership styles have influence on job performance of subordinates.…”
Section: Review Of Literaturementioning
confidence: 92%
“…Mba (2004) states that in this style of leadership, high degree of staff morale is always enhanced. Nwaigwe (2015) in her study on the "influence of head librarians leadership styles on job satisfaction of librarians' in tertiary institution libraries in Imo State, Nigeria", found out that democratic leadership style was the commonest style of leadership adopted by head librarians in tertiary institutions. Out of a population of sixty-five (65) respondents who were part of the survey, 33(54%) of respondents posed for Democratic style, 18(30%) for Autocratic and 10(16%) for laissez-faire leadership styles.…”
Section: Review Of Literaturementioning
confidence: 99%